ChemInform Abstract: Synthesis, Crystal Structure and Physical Properties of [Li0.85Fe0.15OH][FeS]. Issue 29 (July 2015) - Zhang, Xian; Lai, Xiaofang; Yi, Na; He, Jianqiao; Chen, Haijie; Zhang, Hui; Lin, Jianhua; Huang, Fuqiang
Abstract Phase‐pure [Li0.85Fe0.15OH][FeS] is prepared by hydrothermal reaction of Fe, (NH2)2CS, and LiOH (autoclave, 200 °C, 3 d).